THE CORRELATION BETWEEN STIGMA AND FAMILY BURDEN IN CARING FOR PEOPLE WITH MENTAL DISORDERS - Nurazizah, Nurazizah; Fitriani, Nurlaila; Harisa, Akbar (Psychiatry Nursing Journal (Jurnal Keperawatan Jiwa), 2025)
Introduction: South Sulawesi has a high prevalence of mental disorders, affecting 8.8% of households. However, limited public awareness about mental health perpetuates stigma toward individuals with mental disorders and their families, significantly increasing the burden on caregivers. This study aims to identify the relationship between stigma and the caregiving burden experienced by families of individuals with mental disorders at Dadi Regional Special Hospital in South Sulawesi Province. Method: This study is a quantitative study with a Cross-Sectional research design. The dependent variable is family burden and the independent is stigma. The sampling technique used was purposive sampling involving 94 respondents using the Stigma Items questionnaire from SCAN and the Zarit Burden Interview (ZBI). Data analysis included univariate analysis to outline frequency distributions and percentages of the variables, alongside bivariate analysis to assess the correlation between stigma and family burden through the Spearman rank correlation test. Results: The results indicated that over half (58.5%) of families reported low stigma, while 51.1% experienced a mild to moderate burden. Statistical analysis using the Spearman correlation test revealed a significant relationship between stigma and family burden (p = 0.000 < 0.05). The correlation coefficient (r = 0.522) reflects a strong positive relationship, suggesting that increased stigma correlates with higher family burden among those caring for individuals with mental disorders. Conclusions: There is a strong correlation between stigma and family burden in caring for people with mental disorders at Dadi Regional Special Hospital in South Sulawesi Province.